A Thermostable phytase from Neosartorya spinosa BCC 41923 and its expression in Pichia pastoris - Patcharaporn Pandee (2018)
A phytase gene was cloned from Neosartorya spinosa BCC 41923. The gene was 1,455 bp in size, and the mature protein contained a polypeptide of 439 amino acids. The deduced amino acid sequence contains the consensus motif (RHGXRXP) which is conserved among phytases and acid phosphatases. Five possible disulfide bonds and seven potential N-glycosylation sites have been predicted. The gene was expressed in Pichia pastoris KM71 as an extracellular enzyme. The purified enzyme had specific activity of 30. 95 U/mg at 37°C and 38. 62 U/mg at 42°C. Molecular weight of the deglycosylated recombinant phytase, determined by SDS-PAGE, was approximately 52 kDa. The optimum pH and temperature for activity were pH 5. 5 and 50°C. The residual phytase activity remained over 80% of initial activity after the enzyme was stored in pH 3. 0 to 7. 0 for 1 h, and at 60% of initial activity after heating at 90°C for 20 min. The enzyme exhibited broad substrate specificity, with phytic acid as the most preferred substrate. Its K < inf > m < /inf > and V < inf > max < /inf > for sodium phytate were 1. 39 mM and 434. 78 U/mg, respectively. The enzyme was highly resistant to most metal ions tested, including Fe < sup > 2+ < /sup > , Fe < sup > 3+ < /sup > , and Al < sup > 3+ < /sup > . When incubated with pepsin at a pepsin/phytase ratio of 0. 02 (U/U) at 37°C for 2 h, 92% of its initial activity was retained. However, the enzyme was very sensitive to trypsin, as 5% of its initial activity was recovered after treating with trypsin at a trypsin/phytase ratio of 0. 01 (U/U). © 2011 The Microbiological Society of Korea and Springer-Verlag Berlin Heidelberg.